2013 35th International Conference on Software Engineering (ICSE) 2013
DOI: 10.1109/icse.2013.6606654
|View full text |Cite
|
Sign up to set email alerts
|

Predicting bug-fixing time: An empirical study of commercial software projects

Abstract: For a large and evolving software system, the project team could receive many bug reports over a long period of time. It is important to achieve a quantitative understanding of bugfixing time. The ability to predict bug-fixing time can help a project team better estimate software maintenance efforts and better manage software projects. In this paper, we perform an empirical study of bug-fixing time for three CA Technologies projects. We propose a Markov-based method for predicting the number of bugs that will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(107 citation statements)
references
References 22 publications
3
102
0
2
Order By: Relevance
“…We used a dichotomic variable for the IFT, since by analyzing the distribution of IFTs we found that in line with previous studies (Zhang et al 2013), they are distributed as a long-tail distribution (power law). Variables with a logarithmic distribution do not fit well with linear models due to their large variations; this led us to use a logistic regression model, since it fit better with logarithmic distributions.…”
Section: Team Productivitysupporting
confidence: 62%
See 1 more Smart Citation
“…We used a dichotomic variable for the IFT, since by analyzing the distribution of IFTs we found that in line with previous studies (Zhang et al 2013), they are distributed as a long-tail distribution (power law). Variables with a logarithmic distribution do not fit well with linear models due to their large variations; this led us to use a logistic regression model, since it fit better with logarithmic distributions.…”
Section: Team Productivitysupporting
confidence: 62%
“…This renders team Productivity as a binary variable. The approach has already been demonstrated successfully in and Zhang et al (2013).…”
Section: Experimental Designmentioning
confidence: 98%
“…• consider a↵ects in models for bug fixing time estimation [23]. Ortu et al [12] showed that bug fixing time correlate with the a↵ects expressed by developers in issue comments.…”
Section: Research Opportunitiesmentioning
confidence: 99%
“…For example, severity identification [14] targets to identify the status of bug reports for further scheduling in bug management; time expectation of bugs [29] models the time cost of bug deception and expects the time rate of specified bug reports; reopened-bug analysis [20], [30] finds the wrongly fixed bug reports to evade deferring the software release.…”
Section: ) Bug Triagementioning
confidence: 99%